Emergence and spread of a sub-lineage of SARS-CoV-2 Alpha variant B.1.1.7 in Europe, and with further evolution of spike mutation accumulations shared with the Beta and Gamma variants - Stadtmüller, Marlena; Laubner, Alexa; Rost, Fabian; Winkler, Sylke; Patrasová, Eva; Šimůnková, Lenka; Reinhardt, Susanne; Beil, Johanna; Dalpke, Alexander H; Yi, Buqing (Virus evolution, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) evolution plays a significant role in shaping the dynamics of the coronavirus disease 2019 pandemic. To monitor the evolution of SARS-CoV-2 variants, through international collaborations, we performed genomic epidemiology analyses on a weekly basis with SARS-CoV-2 samples collected from a border region between Germany, Poland, and the Czech Republic in a global background. For identified virus mutant variants, active viruses were isolated and functional evaluations were performed to test their replication fitness and neutralization sensitivity against vaccine-elicited serum neutralizing antibodies. Thereby we identified a new B.1.1.7 sub-lineage carrying additional mutations of nucleoprotein G204P and open-reading-frame-8 K68stop. Of note, this B.1.1.7 sub-lineage is the predominant B.1.1.7 variant in several European countries such as Czech Republic, Austria, and Slovakia. The earliest samples belonging to this sub-lineage were detected in November 2020 in a few countries in the European continent, but not in the UK. We have also detected its further evolution with extra spike mutations D138Y and A701V, which are signature mutations shared with the Gamma and Beta variants, respectively. Antibody neutralization assay of virus variant isolations has revealed that the variant with extra spike mutations is 3.2-fold less sensitive to vaccine-elicited antibodies as compared to the other B.1.1.7 variants tested, indicating potential for immune evasion, but it also exhibited reduced replication fitness, suggesting lower transmissibility. The wide spread of this B.1.1.7 sub-lineage was related to the pandemic waves in early 2021 in various European countries. These findings about the emergence, spread, evolution, infection, and transmission abilities of this B.1.1.7 sub-lineage add to our understanding about the pandemic development in Europe and highlight the importance of international collaboration on virus mutant surveillance.